Narrative Inquiry into Teachers as Facilitators in Thematic Learning: Integrating Islamic Values in Elementary Education - Ari Susetiyo; Riska Latifatul Husna; Abdul Muid; Yona Wahyuningsih; Zohaib Hassan Sain (Yayasan Adra Karima Hubbi, 2026)
Background. Teachers play a crucial role as facilitators in creating meaningful learning experiences, particularly in thematic learning that integrates multiple subjects. However, previous studies on teacher facilitation tend to focus on general pedagogical practices and lack strong theoretical integration, especially within Islamic educational contexts. Purpose. This study aims to examine Grade 5 teachers’ understanding and implementation of their role as facilitators in thematic learning at an Islamic elementary school, as well as to explore its theoretical contribution to facilitation practices. Method. This research employed a qualitative case study approach conducted at Sabilul Huda Asy’ari Integrated Islamic Elementary School. Data were collected through classroom observations, in-depth interviews with teachers, students, parents, and the school principal, and documentation analysis. Data analysis involved coding, theme generation, and triangulation to ensure the credibility and validity of the findings. Results. The findings reveal that the teacher’s role as a facilitator is multidimensional, encompassing patience, respect, teacher–student relationships, humility, adaptive teaching strategies, structured lesson planning, motivational support, and collaborative learning facilitation. These dimensions operate as an integrated system that supports students’ cognitive, social, emotional, and moral development. The integration of Islamic values was also found to play a significant role in shaping meaningful learning interactions. Conclusion. This study proposes the Islamic Constructivist Facilitation Model, which conceptualizes teacher facilitation as a holistic process integrating constructivist learning, socio-cultural interaction, and value-based education. The findings highlight that effective facilitation extends beyond instructional practices to include relational, motivational, and moral dimensions, offering important implications for developing holistic teaching practices in elementary education.